Habilidades científicas na formação inicial de professor de ciências : contribuições de atividades experimentais investigativas - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The contributions of experimental activities performed in the laboratory for the development of abilities, learning concepts, understanding of the nature of science and attitudes in students are undeniable. However, closed and decontextualized experimental procedures in science laboratories still predominate. This dissertation aims to identify the possibilities, limits and contributions of experimental investigative activities in the laboratory environment for the development of scientific abilities, aiming at initial formation of a Science teacher, which fulfils the guidelines of the Common National Curricular Base. The scientific abilities in this research allude to the processes and methods that scientists use to build knowledge and solve open problems. Thus, the proposition of a problem situation was fundamental in conducting the research, in dialogue with Bachelard's ideas that knowledge has its origin in a question and that the problems are favorable to the formation of the scientific spirit. To achieve our goal, an experiment workshop was developed and applied, based on Investigative Methodology, at the Federal University of Amazonas, in Manaus, with undergraduate students in Physics and Chemistry. The scientific abilities of designing an experiment to test a hypothesis, conducting an application experiment to test a hypothesis, collecting and analyzing experimental data, and communicating ideas were analyzed. As data collection instruments, an initial questionnaire, written activities, analyzed by previously validated rubrics, and interviews conducted after the workshop with the participating undergraduates students were used. It was observed that undergraduate students in the final periods of their courses have many difficulties in developing a hypothesis that leads to the solution of a problem. However, it was found relevant evidence that the other abilities studied can be developed inlaboratory and contribute to improvements in the initial training of science teachers.
Scientific skills in initial teacher education sciences: contributions of experimental investigative activities
Keywords: Professores - Formação; Laboratórios experimentais; Professores de ciência; Atividades Investigativas; Ciência - Experiências; CIÊNCIAS EXATAS E DA TERRA; Formação de professores; Atividades Investigativas; Experimentos; Habilidades Científicas